2016
DOI: 10.1155/2016/4182595
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potential Inhibitors of Aldosterone Synthase from Chinese Herbs Using Pharmacophore Modeling, Molecular Docking, and Molecular Dynamics Simulation Studies

Abstract: Aldosterone synthase (CYP11B2) is a key enzyme for the biosynthesis of aldosterone, which plays a significant role for the regulation of blood pressure. Excess aldosterone can cause the dysregulation of the renin-angiotensin-aldosterone system (RAAS) and lead to hypertension. Therefore, research and development of CYP11B2 inhibitor are regarded as a novel approach for the treatment of hypertension. In this study, the pharmacophore models of CYP11B2 inhibitors were generated and the optimal model was used to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…40 Aldosterone synthase (CYP11B2), one of the broad cytochrome P450 family, regulates the synthesis of aldosterone from cholesterol in the reninangiotensin-aldosterone system. 41,42 Research by Wu et al also revealed the decreased aldosterone level and the increased corticosterone level may allow corticosterone to occupy the type I receptors more easily and increase BP. 43 Additionally, CDCA, DCA, and LCA could induce the mRNA and protein expression of intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) by stimulation of NF-κB and p38 MAPK signaling pathways, thereby causing endothelial dysfunction.…”
Section: Papermentioning
confidence: 99%
“…40 Aldosterone synthase (CYP11B2), one of the broad cytochrome P450 family, regulates the synthesis of aldosterone from cholesterol in the reninangiotensin-aldosterone system. 41,42 Research by Wu et al also revealed the decreased aldosterone level and the increased corticosterone level may allow corticosterone to occupy the type I receptors more easily and increase BP. 43 Additionally, CDCA, DCA, and LCA could induce the mRNA and protein expression of intercellular cell adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) by stimulation of NF-κB and p38 MAPK signaling pathways, thereby causing endothelial dysfunction.…”
Section: Papermentioning
confidence: 99%
“…In recent years, molecular simulation technologies such as pharmacophore model and molecular docking have been utilized for new drug research and development [44,45]. Te HipHop model is used to identify chemical features common to a range of small ligand molecules and automatically generates pharmacophore models based on the superposition of these common characteristic structures; ligand-based pharmacophore strategy has been universally used to screen small molecule-leading compounds in drug development [46].…”
Section: Discussionmentioning
confidence: 99%
“…Based on more than 100 pharmacophore models constructed previously by our laboratory [ 37 , 38 , 39 , 40 , 41 ], the ones matched with DSS were searched and their Fit values compared to the chemical structure of DSS were calculated. The proteins corresponding to pharmacophore models with Fit value >0.7 were selected as source proteins used in the following study [ 42 ].…”
Section: Methodsmentioning
confidence: 99%